2005
DOI: 10.1002/mame.200500211
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Shape Memory Polyurethane‐Polypyrrole Composites for an Electroactive Actuator

Abstract: Summary: Electroactive shape memory composites were prepared using polyurethane block copolymer and conducting polypyrrole by chemical oxidative polymerization. The electrical conductivity, thermal and mechanical properties, and morphology of the composites were investigated, and a voltage‐triggered shape memory effect was demonstrated. The polyurethane synthesized had a transition temperature near 46 °C. The presence of polypyrrole increased the conductivity of the composites, and a high conductivity of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…The sample deformed at a higher temperature (T d = 1.25 T g ) showed a simple sigmoidal increase of stress upon heating, whereas the sample deformed at a lower temperature (T d = 0.75 T g ) exhibited a peak in recovery stress with a much higher magnitude than that expected for the final stress as dictated by the modulus at T > T g . Similar observations of a recovery stress peak during constrained recovery have been reported for SMPs under compression (65,67), tension (56), three-point bending (55,57), and shear (57). In contrast to Tobushi et al (54), this phenomenon was explained in terms of thermal expansion (56) and structural relaxation during the glass transition (58).…”
Section: Thermomechanical Conditioning Of Shape Memory Polymerssupporting
confidence: 78%
See 1 more Smart Citation
“…The sample deformed at a higher temperature (T d = 1.25 T g ) showed a simple sigmoidal increase of stress upon heating, whereas the sample deformed at a lower temperature (T d = 0.75 T g ) exhibited a peak in recovery stress with a much higher magnitude than that expected for the final stress as dictated by the modulus at T > T g . Similar observations of a recovery stress peak during constrained recovery have been reported for SMPs under compression (65,67), tension (56), three-point bending (55,57), and shear (57). In contrast to Tobushi et al (54), this phenomenon was explained in terms of thermal expansion (56) and structural relaxation during the glass transition (58).…”
Section: Thermomechanical Conditioning Of Shape Memory Polymerssupporting
confidence: 78%
“…The use of electric currents as a triggering means for SM effect has also proven successful and was recently reported by Sahoo et al (12,67). Their initial work involved the use of a conductive polymer [polypyrrole (PPy)] as a coating layer of their in-house thermoplastic SMPU.…”
Section: Triggering Mechanismsmentioning
confidence: 95%
“…Current efforts to implement this technology use conducting SMP composites with carbon nanotubes [7], short carbon fibers (SCFs) [8,9,12], and metallic Ni powder [10,11]. The shape memory effect in these types of SMPs have been shown to depend on the filler content, and they exhibit good energy conversion efficiency and improved mechanical properties.…”
Section: Function Of Cnf Paper In Shape Recovery Actuationmentioning
confidence: 99%
“…However, the actuation approach of shape recovery is seriously limited by traditional direct temperature heating procedures. Fortunately, many interesting and valuable studies have been done on the actuation of SMPs or SMP composites, for which shape recovery can not only be induced by external stimuli, such as heating, but can be manipulated by infrared light heating [5], laser light heating [6], electrical resistive heating [7][8][9][10][11][12][13], magnetic fields [14,15] or solvents [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…When filled with 10 vol% of homogenously distributed carbon nanopowder, samples revealed good shape recovery performances; within 90 s of Joule heating (30 V), the shape recoverability was estimated to be between 75 and 80%. Sahoo et al [209] reported on the use of inherently conductive polypyrrole as coating layer for PCL-based SMPU, filled with MWCNTs. In shape recovery tests with bending mode, one specimen containing 20 wt% polypyrrole was able to recover within 25 s between 85 and 90% of its original shape at a constant electric potential of 40 V.…”
Section: Electrically Conductive Smp Compositesmentioning
confidence: 99%